Pengelolaan Konten Media Sosial Instagram @Info_Tuban Dalam Peningkatan Pengikut - Diah Eka Septyami; Saifuddin Zuhri (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
Infotuban uses social media Instagram as a means to share various information. With the number of 100,000 follower accounts, the involvement of followers of the @info_tuban account is still lacking. The purpose of this study is to find out how the management of social media content on Instagram @info_tuban includes the share, optimize, manage, and engage. This research uses a qualitative descriptive research type. Data collection techniques through interviews, observation, and literature study. The informant determination technique used in this research is purposive sampling technique. This study uses two sources of data, namely primary data obtained from observations and interviews and secondary data obtained through books, internet, literature. The results show that in the share stage @info_tuban uses Instagram as a means of delivering effective and communicative information to build public trust. At the optimize stage, to find out what the public is talking about @info_tuban using the manual method, namely through the Instagram story and hashtag features. In the manage stage , @info_tuban has carried out several activities. However, at this stage @info_tuban does not use social media tools. The last stage engage, @info_tuban has collaborated with people who have influence. To reach the target audience, it is done by regularly posting content.